2015
DOI: 10.1080/15384101.2015.1014146
|View full text |Cite
|
Sign up to set email alerts
|

Impaired light detection of the circadian clock in a zebrafish melanoma model

Abstract: The circadian clock controls the timing of the cell cycle in healthy tissues and clock disruption is known to increase tumourigenesis. Melanoma is one of the most rapidly increasing forms of cancer and the precise molecular circadian changes that occur in a melanoma tumor are unknown. Using a melanoma zebrafish model, we have explored the molecular changes that occur to the circadian clock within tumors. We have found disruptions in melanoma clock gene expression due to a major impairment to the light input pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
1
7
0
2
Order By: Relevance
“…While the animal-type CRY2 (zCRY2) and zCRY4 have only weak or no transcriptional repression ability for the CLOCK:BMAL complex, the four animal-type CRY1s have strong transcriptional repression abilities 14 , so may not only be involved in the circadian clock but also in clock-associated functions, such as the photoperiodic response. Although daily zCry expression patterns have been investigated both in vivo [2][3][4][5][6]8,11 and in vitro 7,9,10 , we comparatively reinvestigated the spatiotemporal expression profiles and light-responsiveness of zCrys to test the above hypothesis. We found that zCry1ab expression in the eye changes depending on the day length.…”
Section: Continuedmentioning
confidence: 99%
“…While the animal-type CRY2 (zCRY2) and zCRY4 have only weak or no transcriptional repression ability for the CLOCK:BMAL complex, the four animal-type CRY1s have strong transcriptional repression abilities 14 , so may not only be involved in the circadian clock but also in clock-associated functions, such as the photoperiodic response. Although daily zCry expression patterns have been investigated both in vivo [2][3][4][5][6]8,11 and in vitro 7,9,10 , we comparatively reinvestigated the spatiotemporal expression profiles and light-responsiveness of zCrys to test the above hypothesis. We found that zCry1ab expression in the eye changes depending on the day length.…”
Section: Continuedmentioning
confidence: 99%
“…Skin is a complex organ consisted of different cell types. [34] Skin is a complex organ consisted of different cell types. It has to be clarified whether expression levels for clock genes are different among the variety of cell types of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…There is also an abundance of epidemiological data showing a link between shift work and cancer incidence in humans [76]. Zebrafish have also added to this area of investigation [77]. Using luminescent report animals, containing the per3-luciferase gene, it is possible to monitor clock function in a developing melanoma, versus that in neighbouring healthy tissue.…”
Section: The Outputsmentioning
confidence: 99%